Quality of coffee dried on suspended terrace with different layers - Joyce Fernandes de Assis; Bruno Manoel Rezende de Melo; Sindynara Ferreira (Revista Agrogeoambiental)
Seeking to improve the final quality of coffee, producers began to improve and innovate in all stages of this segment to meet the demanding market. Hence, this study evaluated the physicochemical and sensory quality of dried unripe, cherry and over-ripe coffee cherries on suspended terraces in different layers. The experiment involved drying coffee in all layers of the suspended terraces, consisting of seven treatments and four replications as follows: T1– concrete terrace; T2 – conventional “single-layer” suspended terrace; T3 – first layer “suspended terrace with two layers”; T4 – second layer “suspended terrace with two layers”; T5 – first layer “suspended terrace with three layers”; T6 – second layer “suspended terrace with three layers”; and T7 – third layer “suspended terrace with three layers.” All treatments used identical samples composed of a mixture of coffee cherries in the three different physiological maturation stages (unripe, cherry and over-ripe). Percentage of each stage was evaluated in a one-liter container with coffee. Physicochemical and sensory quality of unripe, cherry and overripe coffees is influenced by the terrace structure. Treatments T5 and T6, represented by the first layer “suspended terrace with three layers” and second layer “suspended terrace with three layers,” presented the best results for the beneficial fermentation caused by the terrace structure, providing a more shaded environment and resulting in desirable sensory attributes.